Alterations of skeletal muscle microcirculation detected by blood oxygenation level-dependent MRI in a patient with granulomatosis with polyangiitis - Jacobi, Björn; Schulte, Anja-Carina; Partovi, Sasan; Michel, Sandra; Karimi, Sasan; Lyo, John K.; Daikeler, Thomas; Aschwanden, Markus; Staub, Daniel; Zipp, Lisa; Rasmus, Matthias; Huegli, Rolf W.; et al. (Rheumatology, 2013)
Disclosure statement: M.R.'s institute has a scientific collaboration with Siemens and an unrestricted research fund from Bayer Health Care. G.B. has received unrestricted grants from Bayer Healthcare, Switzerland and Siemens Medical Systems, Switzerland. All other authors have declared no conflicts of interest.These findings strongly suggest major perturbations of skeletal muscle microcirculation in this GPA patient, revealed by skeletal muscle BOLD MRI. The lower T2*min value in the patient might be explained by increased oxygen consumption as control and patient showed comparable baseline absolute T2* values, and the IDS absolute value was substantially higher in the patient. This might be a compensatory mechanism for chronic hypoxic conditions in patients with GPA. T2*max decrease could be explained by reduced blood flow in skeletal muscle microvessels, owing to small vessel vasculitis. The underlying mechanisms of the detected BOLD alterations have to be interpreted with care owing to other T2* influencing factors such as blood volume, haematocrit, functional vascular status and metabolic changes [5, 7]. Owing to the lack of reference methods for the measurement of perfusion or oxygenation, our findings remain mostly descriptive. However, the measured BOLD response in GPA is different from previous results in patients with atherosclerosis that showed diminished ischaemic T2* decline and a prolonged TTP [5, 10]. This may indicate that other mechanisms besides accelerated atherosclerosis play an important role in the pathogenesis of skeletal muscle microcirculation alterations in GPA. Of course, further studies with larger patient collectives are warranted to elucidate the underlying mechanisms of the described BOLD signal alterations in GPA.
Gesehen am 18.03.2021
First published: 30 July 2012